Particle filter-based multi-path time-varying channel blind equalization in stable noise - Nan XIA; Tian-shuang QIU; Jing-chun LI (Tongxin xuebao)
A particle filtering (PF) based blind equalization algorithm for the multi-path time-varying channel was pre-sented and a delay sampling blind equalization algorithm was proposed. The contribution of the novel algorithm can be summarized as follows: the blind sequential algorithm was derived which performs the maximum a posteriori (MAP) symbol detection in symmetric-alpha-stable (SaS) distribution noise; and the joint posterior distribution of the Gaussian approximation for SaS distribution noise and the joint posterior distribut nknown channel and noise parameters were derived and presented. The simulation results demonstrate that the proposed method is valid and outperforms the existing algorithms,especially in the case of strong impulsive noise.